Deconstructing Chronic Low Back Pain in the Older Adult—Step by Step Evidence and Expert‐Based Recommendations for Evaluation and Treatment: Part I: Hip Osteoarthritis. Issue 5 (3rd April 2015) - Weiner, Debra K.; Fang, Meika; Gentili, Angela; Kochersberger, Gary; Marcum, Zachary A.; Rossi, Michelle I.; Semla, Todd P.; Shega, Joseph
Abstract Objective To present the first in a series of articles designed to deconstruct chronic low back pain (CLBP) in older adults. The series presents CLBP as a syndrome, a final common pathway for the expression of multiple contributors rather than a disease localized exclusively to the lumbosacral spine. Each article addresses one of twelve important contributors to pain and disability in older adults with CLBP. This article focuses on hip osteoarthritis (OA). Methods The evaluation and treatment algorithm, a table articulating the rationale for the individual algorithm components, and stepped‐care drug recommendations were developed using a modified Delphi approach. The Principal Investigator, a five‐member content expert panel and a nine‐member primary care panel were involved in the iterative development of these materials. The algorithm was developed keeping in mind medications and other resources available within Veterans Health Administration (VHA) facilities. As panelists were not exclusive to the VHA, the materials can be applied in both VHA and civilian settings. The illustrative clinical case was taken from one of the contributor's clinical practice. Results We present an algorithm and supportive materials to help guide the care of older adults with hip OA, an important contributor to CLBP. The case illustrates an example of complex hip‐spine syndrome, in which hip OA was an important contributor to disability in an older adult with CLBP. Conclusions Hip OA is common and should be evaluated routinely in the older adult with CLBP so that appropriately targeted treatment can be designed.